The Role of Dynamic Assessment in Academic Writing: A Review Study - Abdalkarim Amin, Aras; Farooq Jawad, Hoshang (The Scientific Journal of Cihan University– Sulaimaniya, 2023)
Assessment is an approach which is adopted in the educational process as a means to identify the learners’ knowledge in the performance of language diagnosing the lacks and the needs. Various types of assessments have been introduced to serve the educational process. This article reviews the types of assessments through a theoretical framework concentrating in particular on one of the alternatives of assessment, namely dynamic assessment by relying on Vygotsky’s sociocultural theory on which it is mainly drawn. The paper focuses on this type of assessment in relation to the learners’ writing skills. Based on the reviewed studies, it is demonstrated that DA application can enhance the writing skill of learners since it satisfies the needs of the learners because there is face-to-face interaction. The study shows that DA integrates teaching and assessment simultaneously which minimizes the anxiety of the learners while they have the task of writing academically. It also shows that DA has a pivotal role to identify the learners’ weaknesses at various levels assisting teachers to know where the gaps are and to take a step in advance for a better future performance.